Інноваційні вектори управління - Пономарьов, Олександр Семенович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Показано, що управління є визначальною умовою успішного здійснення діяльності й забезпечення бажаної її ефективності. Відомо, що в умовах інноваційного типу суспільного розвитку важливою проблемою постає розробка і системне застосування інноваційних управлінських технологій. Проаналізовано дослідження і публікації з проблем визначення інноваційних векторів управління. Вони далеко не вичерпують всіх її важливих аспектів. Йдеться про соціальні, економічні, організаційні та психологічні умови і можливості забезпечення як інноваційного характеру самого управління, так і його відповідності вимогам індустрії 4.0. Недостатньо розкрито також сенс і особливості інноваційного управління та його впровадження в практику управлінської діяльності. За результатами системного дослідження широкого спектру проблем управління й аналізу літературних джерел із цих проблем цілями статті визначено розмежування сенсу понять інноваційності, ефективності та відповідності змісту й характеру управління суспільним вимогам та очікуванням його переходу на рівень 4.0.

It is shown that management is not just one of the integral components of the joint activity of people, but also a determining condition for its successful implementation and ensuring the desired efficiency. It is known that the development of management ideology and technology usually lags behind production technologies. This applies to both local and global aspects of management. Therefore, today, in the conditions of an innovative type of social development, the development and systematic application of innovative management technologies becomes an important problem. Research and publications on the problems of determining innovative management vectors are analyzed. They are far from exhausting all its important aspects. It is about social, economic, organizational and psychological conditions and possibilities of ensuring both the innovative nature of the management itself and its compliance with the requirements of Industry 4.0. The meaning and features of innovative management and its implementation in the practice of managerial activity are also insufficiently disclosed. According to the results of a systematic study of a wide range of management problems and the analysis of literary sources on these problems, the goals of the article are to distinguish the meaning of the concepts of innovation, efficiency, and compliance of the content and nature of management with social requirements and expectations of its transition to level 4.0.
Innonative management vectors
Keywords: вектори управління; управлінські технології; інноваційність; індустрія 4.0; management vectors; management technologies; innovation, industry 4.0